EVALUASI SISTEM PENGENDALIAN INTERN (INTERNAL CONTROL) TERHADAP KINERJA DINAS PEKERJAAN UMUM PROVINSI SULAWESI UTARA - Turangan, Julia Christina; Saerang, David Paul Elia; Pusung, Rudy J. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Implementation of internal control system is needed so that activities can be implemented effectively and efficiently, and generate a reliable reports. As one of the public sector organization, Dinas Pekerjaan Umum Provinsi Sulawesi Utara also requires internal control for the effectiveness and efficiency of their activities and produce a reliable reporting to reduce abuse of authority from irresponsible parties. The purpose of this research is to evaluate the system of internal control on performance of Dinas Pekerjaan Umum Provinsi Sulawesi Utara. The method that used in this research is qualitative research methods with data analisys technique is data reduction, presentation of data, and conclusions. The results of this study are internal controls applied by Dinas Pekerjaan Umum Provinsi Sulawesi Utara has been effective and adequate. Realization of expenditure Dinas Pekerjaan Umum Provinsi Sulawesi Utara from 2013 to 2015 has been effective.Keywords : Evaluation, Internal control, Performance